Managing wastes from aluminum smelter plants - Mazumder, B. (Woodhead Publishing India, 2011)
Managing wastes from aluminium smelter plants discusses major environmental polluting waste material from aluminum industries and, particularly, spent pot liner. The book incorporates the authors' direct experience in handling this toxic waste, decontaminating spent pot liner and recovering its carbon value.
Keywords: Aluminum -- Metallurgy -- Waste disposal.; elektronické knihy; electronic books